2015
DOI: 10.1007/s00586-015-3979-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous wound infusion of ropivacaine for the control of pain after thoracolumbar spinal surgery: a randomized clinical trial

Abstract: Purpose A prospective randomized clinical trial was carried out to observe the analgesic efficacy of ropivacaine for postoperative pain following thoracolumbar spinal surgery. Methods Seventy-one patients with elective posterior thoracolumbar spinal surgery were randomly divided into two groups. Local group received 0.33 % ropivacaine by pump through the wound, and intravenous group received flurbiprofen axetil, pentazocine and palonosetron via intravenous pump. We evaluated the level of pain, the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 17 publications
(20 reference statements)
1
32
0
1
Order By: Relevance
“…Only seven studies performed a formal intention-to-treat analysis (Albi-Feldzer 2013; Kairaluoma 2006; Karmakar 2014; Kurmann 2015; Singh 2007; Sprung 2006; Terkawi 2015b). In four studies, there was no attrition at all (Comez 2015; Grigoras 2012; ; ; Weber 2007; Xu 2017). …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Only seven studies performed a formal intention-to-treat analysis (Albi-Feldzer 2013; Kairaluoma 2006; Karmakar 2014; Kurmann 2015; Singh 2007; Sprung 2006; Terkawi 2015b). In four studies, there was no attrition at all (Comez 2015; Grigoras 2012; ; ; Weber 2007; Xu 2017). …”
Section: Resultsmentioning
confidence: 96%
“…Some reported double blinding but did not provide details (Bell 2001; Comez 2015; Paxton 1995; Pinzur 1996). Six studies described out-come assessor blinding, without detail on personnel or participant blinding (Burney 2004; Dogan 2016; Ibarra 2011; Lam 2015; Lavand’homme 2005; O’Neill 2012), but nine other studies neither described nor confirmed it (Bell 2001; Choi 2016; Katsuly-Liapis 1996; Liu 2015; Lu 2008; Okur 2016; Wodlin 2011; Xu 2017; Zhou 2016). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In current practice, prolonged nerve blockade can be achieved by repeated injections or by placement of indwelling catheters for continuous infusions of drugs. [8,9] Both approaches are resource intensive, necessitating skilled personnel for administration, adjustment of drug levels, and monitoring of drug effects – both intended (pain relief) and unintended (cardiorespiratory effect). This level of effort and monitoring may require hospitalization and requires patients to be tethered to external devices, which presents a risk of infection.…”
Section: Introductionmentioning
confidence: 99%